Kapan Kewajiban Mahar Menurut Pendapat Ulama’ - Muhammad Khotami Alfarisi; Wahyudi Batubara (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The obligation to dowry in marriage is one of the legal conditions for a marriage contract regulated in Islamic law. Scholars have various views regarding the timing and conditions of dowry obligations, which are based on the arguments of the Koran, Hadith, as well as ijma' and qiyas. This article aims to explain in detail the opinions of the ulama regarding when the dowry obligation applies and how it is implemented in household life. This research uses a literature study method with a descriptive-analytical approach to various classical and contemporary jurisprudence literature. The results of the study show that the dowry obligation arises after the marriage contract is legal according to sharia. The scholars agree that the dowry must be handed over in full if a husband and wife relationship occurs or one of the parties dies. However, if the divorce occurs before the relationship between husband and wife, the clerics agree to pay half of the specified dowry amount. This article also reveals differences in views of ulama regarding the regulation of dowry payments under certain conditions, such as the dowry not being determined at the time of the contract. This study provides important insights for the public in understanding dowry obligations according to Islamic law.